Inovasi Pembelajaran IPS Berbasis Media Sosial: Pemanfaatan Instagram Medan Amrulloh sebagai Sumber Belajar Kontekstual - Inayatu Khoirul Magfiroh; Kusnul Munfa’ati; Fina Dwi Rosita Dewi (IAIN Madura, 2026)
This research was conducted based on various problems still found in Social Studies (IPS) learning, such as the use of less varied teaching methods, minimal innovation in the learning process, and limited access to technology for students in Islamic boarding schools (pesantren). This study aims to analyze the use of Instagram as an innovation in Social Studies learning through content presented by Medan Amruallah. The study used a qualitative approach with a case study method on Instagram posts supported by a literature review. Data were obtained through observations of content characteristics, user interactions, and the educational content contained in the posts. The results show that Medan Amruallah's content has the potential to be an effective learning medium in supporting the delivery of Social Studies material, particularly regarding history, culture, and various social phenomena. The visual, informative, and interactive characteristics of the content are able to attract attention and increase student participation in the learning process. In addition, the use of easy-to-understand language and the connection of the material to social reality also help students understand Social Studies concepts more deeply. Therefore, Instagram can be an alternative, innovative learning medium to support more engaging Social Studies learning and in line with developments in the digital era.